Islam and America through the eyes of Imran Khan - Sorrentino, Bruno; Purdie, John; Khan, Imran (California : NAATA, 1997)
Imran Khan, a Pakistani celebrity cricket player turned politician examines the political, social and economic causes of the schism between Islamic world and the West.
Executive producer, Alan Haylling; film editor, David Hope
Presented by : Imran Khan
Keywords: Islam and politics -- United States; Islam and world politics